Kinetic and physiological responses of Listeria monocytogenes to novel non-thermal inactivation treatments and their application to minimally processed seafood - Bittencourt, CR (2009)
Listeria monocyto genes is a facultative anaerobic pathogen found in soil and water, on vegetation, food contact surfaces and in raw food materials including seafood. It grows at refrigeration temperatures and up to 14% sodium chloride making it almost impossible to control in fresh or minimally-processed seafood under aerobic or anaerobic storage conditions. This thesis considers strategies to control growth of this bacterium on seafood using both established and novel non-thermal technologies and seeks to elucidate physiological mechanisms underlying one of the approaches, namely high pressure processing. Chapter 1 reviews the microbiology of seafood including normal microbiota, spoilage processes, pathogen ecology and occurrence and non-thermal processes that are currently used or have the potential to be utilized by the seafood industry. It serves as reference material for the following chapters. Chapter 2 describes an empirical assessment of several preservatives proposed as antilisterial agents. In collaboration with a local Atlantic salmon smokehouse, three commercially available antimicrobial preparations were applied directly to salmon fillets prior to smoking with the intent to stop Listeria monocyto genes growth on vacuum packed cold smoked salmon (CSS). The challenge trial extended over 40 days at 4¬¨‚àûC and 10¬¨‚àûC. Microbial and sensorial analyses were conducted in parallel. Results showed that two of the three treatments evaluated presented listeriostactic activity. The remaining compound appeared not to penetrate in the salmon flesh and challenge the Listeria monocyto genes introduced to the inner flesh after slicing. From the sensorial point of view one of the successful Listeria monocyto genes growth inhibitors performed slightly better than the other but significantly better than the untreated CSS, making it a good candidate to control the growth of this pathogen in this commodity. A search for novel, cold-active, anti-listerial bacteriocins is the focus of Chapter 3. Specifically, 1600 ...